Evaluasi Perkerasan Runway Bandar Udara Sultan Syarif Kasim (SSK) II Pekanbaru Terhadap Pesawat B737-900 ER Dengan Metode ACN-PCN - Moulana Rizaldi; Ari Sandhyavitri; Alfian Malik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The airport is an air transportation facility which has now become an important part of the movement of people and goods. The growing Indonesian economy, especially the Riau Province and Pekanbaru City, also has a big role in increasing the use of airport facilities. All available facilities must meet service standards including the runway section for aircraft services. As aircraft movements increase every year, it is necessary to evaluate the operational side of pavement conditions, so this study aims to analyze the PCN value of the runway using the ACN-PCN comparison method for the B737-900 ER aircraft. Based on a report issued by the Ministry of Transportation, the PCN value of the existing runway is 66/F/B/X/T. The results of the evaluation using COMFAA show that in 2025, the runway structure needs to be improved to serve the movement of the B737-900 ER aircraft in 2025 which has a PCN value of 48 F/B/X/T, while the ACN value of the aircraft is 49,8 with a total aircraft movement of reaching 69,369 aircraft per year. Keywords: runway,facility, evaluate, aircraft movement, existing